2022
DOI: 10.1108/ijchm-01-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Translating responsible leadership into team customer relationship performance in the tourism context: the role of collective job crafting

Abstract: Purpose This study aims to unravel the role of teams’ job crafting in translating responsible leadership into their customer relationship performance. Design/methodology/approach The data were gathered from 87 managers and 608 employees from tour companies. The data analysis was performed via multilevel structural equation modeling. Findings The results demonstrated that crafting of team tasks played a mediating role for the link of responsible leadership to the team’s customer relationship performance. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 142 publications
(255 reference statements)
0
5
0
Order By: Relevance
“…First, most existing research on responsible leadership in the service industry primarily examines its effects at the individual and team levels, such as employees’ green behavior (Luu, 2022a), organizational citizenship behavior (Freire and Gonçalves, 2021; Zhao and Zhou, 2019) and team’s customer relationship performance (Luu, 2022b). Only a limited number of qualitative studies have investigated CEO responsible leadership’s effect on organizational-level outcomes (Jiang et al , 2022; Maak et al , 2016; Varma, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, most existing research on responsible leadership in the service industry primarily examines its effects at the individual and team levels, such as employees’ green behavior (Luu, 2022a), organizational citizenship behavior (Freire and Gonçalves, 2021; Zhao and Zhou, 2019) and team’s customer relationship performance (Luu, 2022b). Only a limited number of qualitative studies have investigated CEO responsible leadership’s effect on organizational-level outcomes (Jiang et al , 2022; Maak et al , 2016; Varma, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics highlight the relevance of responsible leadership to service organizations. However, existing research on responsible leadership in the service context has primarily focused on its impact at individual and team levels (Cheng et al , 2022; Freire and Gonçalves, 2021; Luu, 2022b), largely overlooking its influence on service organizations’ outcomes. This study aims to bridge these research gaps by exploring the effects that CEO responsible leadership exhibits on CSR and organization performance within service organizations while also discovering the mediating role of diverse organizational climates and the moderating effect of CEO founder status.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Vietnamese hotels have been chosen for our research because the country’s hospitality sector can provide a rich context for our research (Hoang et al , 2023). Vietnamese hospitality industry has fast developed in the last two decades since Vietnam's participation in the WTO (Luu, 2018; Nguyen et al , 2021), which requires Vietnamese hotels to enhance service innovation to compete with international hotels (Luu, 2023). Furthermore, recent research revealed that Vietnamese customers, particularly in the tourism and hospitality sectors, have become increasingly demanding (Luu, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Welch and Welsh (2005) stated that "when you become a leader, success is all about growing others" (p. 61). To induce job crafting among their subordinates, supervisors not only have to provide training and rewards but more importantly, they have to practice job crafting behaviors themselves (Luu, 2022). However, additional research is needed to explain how supervisors' job crafting may influence subordinates and, thus, improve their work performance (Yadav and Dhar, 2021;Luu, 2022).…”
Section: Introductionmentioning
confidence: 99%